Konstruowanie kultury osiągnięć w szkole - Urszula Dernowska (Problemy Wczesnej Edukacji)
Building the culture of a school takes time and effort. The culture of the school is not something that can be left to chance, nor can it be seen as something beyond our control. Having a mission is an important step in improving student achievement. It focuses people inside the place called school on a common purpose. According to Douglas Fisher, Nancy Frey, and Ian Pumpian, five pillars that hold up the mission statement are presented: welcome, do no harm, well chosen words, it’s never too late to learn, and efficacy and reflection. These pillars are critical to building a culture of achievement in school. The author also makes a few comments on some aspects of Polish school reform.